What’s Your Platform? Introducing the Platform Theory in Agricultural Communication - Sudarshan Adhikari; Suraksha Baral (Journal of International Agricultural and Extension Education, 2025)
Platform theory is broadening its scope across disciplines. In the current literatures, its applicability has been specially documented in the study of digital platforms which have dynamic nature and cannot be explained fully by traditional linear approaches. In this paper, we claim its applicability in agricultural communication scholarship and practices. Because the agricultural communication involves numerous stakeholders and several platforms working at the same time to result in a complex relationship among the involved elements, platform theory may best help to understand the complex scenario developed on the communication system. Finally, we propose a conceptual framework to explain the general outlook of platform theory in agricultural communication. We argue that this framework will serve as a model to understand complex and dynamic agricultural communication system.
Keywords: platform; platform theory; agricultural communication; extension; framework